2006
DOI: 10.1016/j.jchromb.2005.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Measuring environmental phenols and chlorinated organic chemicals in breast milk using automated on-line column-switching–high performance liquid chromatography–isotope dilution tandem mass spectrometry

Abstract: Breast milk is one possible route of exposure to environmental chemicals, including phenols and chlorinated organic chemicals for breast-fed infants. We developed a highly sensitive method of analyzing breast milk for triclocarban (3,4,4 -trichlorocarbanilide) and eight phenolic compounds: bisphenol A (BPA), 4-tert-octylphenol (4-tOP), ortho-phenylphenol (OPP), 2,4-dichlorophenol, 2,5-dichlorophenol, 2,4,5-trichlorophenol, 2,4,6-trichlorophenol, and 2-hydroxy-4-metoxybenzophenone (BP-3). The method includes ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
3
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(126 citation statements)
references
References 16 publications
(19 reference statements)
3
113
3
5
Order By: Relevance
“…Bisphenol A was measured after enzymatic hydrolysis of conjugates. Ye et al (2006) found measurable concentrations of bisphenol A in milk samples from 18 of 20 lactating women. Free bisphenol A was found in samples from 12 women.…”
Section: Technical Products and Impuritiesmentioning
confidence: 89%
See 1 more Smart Citation
“…Bisphenol A was measured after enzymatic hydrolysis of conjugates. Ye et al (2006) found measurable concentrations of bisphenol A in milk samples from 18 of 20 lactating women. Free bisphenol A was found in samples from 12 women.…”
Section: Technical Products and Impuritiesmentioning
confidence: 89%
“…There were no differences between pregnant and non-pregnant blood levels (median in mg/L 0.44, range 5 0.22-0.87; mean1SD 5 0.4610.20) . Median bisphenol A concentrations in human milk were reported to be r1.4 mg/L Ye et al, 2006). One of the studies reported a milk/serum ratio of 1.3 .…”
Section: Summary Of General Toxicology and Biologicmentioning
confidence: 99%
“…In our exposure ranking system, it ranked 12th out of 37 test compounds ( Table 1). Considering that ortho-phenyl phenol was highly ranked by exposure and that non agricultural sources were absent from our exposure scores, it is not surprising that it was detected in all human urine samples tested in two studies [mean concentration, 2.9 nM, n = 30 samples (Ye et al 2005); 35.2 nM, n = 22 samples (Bartels et al 1997)], 85% of breast milk samples [mean concentration, 10.6 nM, n = 20 samples (Ye et al 2006)], and 30% of amniotic fluid samples [mean concentration, 0.76 nM, n = 20 samples (Bradman et al 2003)] in the United States. ortho-Phenyl phenol was previously identified as a receptor-mediated anti androgen (Kojima et al 2004), but no data are available on its possible effects in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Sun et al (2004) detected unconjugated BPA (range, 0.28-0.97 ng/mL; mean, 0.61 ng/mL) in the breast milk of 100% of the women studied. A third study detected unconjugated BPA in 60% of samples (mean, 1.3 ng/mL milk) and total BPA in 90% (mean, 1.1 ng/mL milk) (Ye et al 2006). In the fourth study, Ye et al (2008a) detected unconjugated and total BPA in all four of the samples examined.…”
Section: Bpa Exposure Assessment In Breast Milkmentioning
confidence: 93%